EFFECTS OF CONFLICTS ON BUILDING CONSTRUCTION PROJECTS OF SINDH, PAKISTAN - Abbasi, Saifullah; Memon, Nafees Ahmed; Vighio, Anees; Raza, Muhammad Saleem (Tropical Scientific Journal, 2023)
ABSTRACT Objective: This paper aims to identify and rank effects of conflict in the construction industry of Sindh, Pakistan according to its importance. Research Method: A thorough analysis of the relevant literature was carried out to identify the effects of conflicts. Unstructured interviews were held to gain a deeper insight. Based on the identified effects from the literature review and interviews, a survey was carried out in Sindh, Pakistan's construction sector using a questionnaire. The data was reviewed and the effects were rated using IBM SPSS. Findings: Results shows that in Sindh construction industry deterioration in work quality, a time overrun, and a cost overrun are top most significant negative effect of conflict, while behavioral responses like smoking, alcohol consumption and being hostile and the erosion of personal relationships are the least important causes of conflict Originality: This paper's goal is to identify and rank the impacts of conflict on the construction sector in Sindh, Pakistan, so that stakeholders in building projects can make more informed decisions. Insights into conflict management that come from this study are anticipated to be novel. In addition, the study sheds light on the most significant repercussions of conflicts in the construction industry, helping those involved in the industry make more informed decisions. Keywords: Negative Effects, Conflicts, Construction Industry